Inhibitory Effects of Polaprezine on the Inflammatory Response to Helicobacter pylori - Osamu Handa; Norimasa Yoshida; Yukiko Tanaka; Miho Ueda; Takeshi Ishikawa; Tomohisa Takagi; Naoyuki Matsumoto; Yuji Naito; Toshikazu Yoshikawa (Canadian Journal of Gastroenterology)
Helicobacter pylori-infected gastrointestinal mucosa is frequently infiltrated by polymorphonuclear leukocytes (PMN) and monocytes, and these invading cells have been implicated in gastrointestinal mucosal inflammation. To clarify the efficacy of polaprezinc, a chelate compound consisting of zinc and L-carnosine, against H pylori-induced inflammation including PMN infiltration, the in vitro effects of this drug on interleukin (IL)-8 production by an established gastric cancer cell line (MKN 45 cells) and on PMN-endothelial cell adhesive interactions was investigated. Polaprezinc and zinc sulphate inhibited IL-8 production by MKN 45 cells in response to stimulation with H pylori water extract (HPE) in a dose-dependent manner from 10-7 M to 10-5 M. In addition, the expression of CD11b and CD18 on PMN and PMN-dependent adhesion to endothelial cells elicited by HPE was inhibited by polaprezinc and zinc sulphate in a concentration-dependent manner. L-carnosine did not have any effects on IL-8 production or PMN-endothelial cell interactions. These results suggest that polaprezinc, mainly the zinc component, may inhibit H pylori-induced PMN-mediated gastric inflammation by attenuating CD11b/CD18 expression on PMN and IL-8 production from gastric epithelial cells.